Aplikasi Inventori ATK Menggunakan Php dan Mysql pada Puskesmas Benteng Kota Sukabumi - Ridwan; Tia Ernawati (JURNAL BUANA INFORMATIKA CBI, 2020)
Puskesmas Benteng is the technical implementation unit of the Sukabumi City Health Service which is responsible for providing health services in Benteng Village, Warudoyong District, Sukabumi City.The development of the inventory application is expected to make it easier for office stationery procurement officers in carrying out activities of procurement and expenditure of goods as well as inventory reporting. The application is designed with a UML system model and is made using php and mysql Keywords: Puskesmas, UML, Php, MySql